The Southern Cone Model: The Political Economy of Regional Capitalist Development in Latin America - Phillips, Nicola (RIPE Series in Global Political Economy, 2004)
Developing an original blend of perspectives from the fields of international and comparative political economy, this book presents an innovative and in-depth account of the contemporary political economy of the southern cone of Latin America: Argentina, Brazil, Chile, Paraguay and Uruguay. It identifies a new and distinctive model of regional capitalist development emerging in the southern cone and a complex relationship with both the global political economy and the five distinctive national political economies in the region. Ranging across the contours of labour, business, states and regionalist processes, Phillips assesses the significance of the Southern Cone Model for the ways in which we understand contemporary capitalist development at both national and transnational levels. Nicola Phillips is currently Hallsworth Research Fellow at the University of Manchester, UK. Her research and teaching interests fall broadly in the field of International Political Economy and development, with a regional specialisation in the political economy of the Americas. She is co-editor, most recently, of New Regionalisms in the Global Political Economy: Theories and Cases (Routledge, 2003) Part One: Introduction Part Two: The contours of Southern Cone development Part Three: The emerging regional political economy Part Four: Conclusion